Aβ-related memory decline in APOE ε4 noncarriers: Implications for Alzheimer disease. (26th April 2016) - Lim, Yen Ying; Laws, Simon M.; Villemagne, Victor L.; Pietrzak, Robert H.; Porter, Tenielle; Ames, David; Fowler, Christopher; Rainey-Smith, Stephanie; Snyder, Peter J.; Martins, Ralph N.; Salvado, Olivier; Bourgeat, Pierrick; et al.
Abstract : Objective: As the absence of Aβ-related memory decline in APOE ε4 noncarriers may be due to the relative brevity of previous studies, we aimed to characterize Aβ-related cognitive decline over 72 months in APOE ε4 carriers and noncarriers who were cognitively normal (CN). Methods: CN older adults (n = 423) underwent Aβ imaging and APOE genotyping. Participants completed comprehensive neuropsychological testing at baseline 18-, 36-, 54-, and 72-month assessments. Results: Relative to Aβ− CN ε4 noncarriers, both Aβ+ CN ε4 carriers and noncarriers showed significantly increased decline in measures of memory, language, and executive function as well as higher rates of progression to a clinical classification of mild cognitive impairment. Memory decline was greater in Aβ+ CN ε4 carriers than in Aβ+ CN ε4 noncarriers. No cognitive decline was evident in Aβ− CN ε4 carriers. Conclusions: In CN older adults, Aβ+ is associated with memory decline in ε4 noncarriers; however, the rate of this decline is much slower than that observed in ε4 carriers. These data indicate that the processes by which ε4 carriage increases the rate of Aβ-related cognitive decline occur in the preclinical stage of Alzheimer disease.